Development of an MRI-Compatible High-Intensity Focused Ultrasound Phased Array Transducer Dedicated for Breast Tumor Treatment - Kuo, Li-Wei (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
High-intensity focused ultrasound (HIFU) under magnetic resonance imaging (MRI) guidance can achieve a noninvasive and precise ablation of the solid tumor. In the study, an MRI-compatible 1-MHz 16-channel ring-shaped transducer was developed to minimize the burn risk of breast skin and perform volumetric ablation for short treatment time. The measured electroacoustic conversion efficiency of the transducer was 50.90% ± 5. The transducer could produce a point and a quasi-hollow-cylinder lesion in a thermal-sensitive phantom or an ex vivo pork by tuning the phase of each element. It may achieve volumetric ablation of 1.5 cm3 when the point lesion is located inside the hollow lesion. Ex vivo ablation experiments showed that the transducer could cause a coagulative necrosis in the pork from the surrounded subcutaneous fat by 5 mm without fat damage. The temperature and region of the pork ablation were quantified by MRI technique. There was no MRI interference from HIFU and vice versa while both systems operated concurrently